2009
DOI: 10.1182/blood-2009-02-206359
|View full text |Cite
|
Sign up to set email alerts
|

Selective engraftment of donor CD4+25high FOXP3-positive T cells in IPEX syndrome after nonmyeloablative hematopoietic stem cell transplantation

Abstract: Mutations of FoxP3 result in the disturbance of FoxP3 expression and lack of functional CD4 ϩ CD25 high regulatory T cells in humans, causing immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome. The only curative approach for IPEX syndrome, which is fatal within the first year of life in many cases, is allogeneic hematopoietic stem cell transplantation (HSCT). We monitored lineage-specific chimerism in a FoxP3-deficient patient after nonmyeloablative HSCT and graft rejection over 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 9 publications
4
58
0
Order By: Relevance
“…17 Furthermore, the observation that nTregs are present in PBMCs of IPEX patients 10 demonstrates that mut-FOXP3 does not prevent the emergence of nTregs from the thymus, indirectly reinforcing the hypothesis of a peripheral selection of WT-FOXP3 nTregs in carriers. Interestingly, long-term survival of donor-derived nTregs, despite the loss of donor peripheral chimerism in other cell populations, has been demonstrated in an IPEX patient who successfully underwent bone marrow transplantation, 18 further supporting the evidence that nTregs expressing the WT-FOXP3 allele have a selective advantage.…”
Section: Carriers Of Foxp3 Mutations Have Functionally Normal Ntregs mentioning
confidence: 65%
“…17 Furthermore, the observation that nTregs are present in PBMCs of IPEX patients 10 demonstrates that mut-FOXP3 does not prevent the emergence of nTregs from the thymus, indirectly reinforcing the hypothesis of a peripheral selection of WT-FOXP3 nTregs in carriers. Interestingly, long-term survival of donor-derived nTregs, despite the loss of donor peripheral chimerism in other cell populations, has been demonstrated in an IPEX patient who successfully underwent bone marrow transplantation, 18 further supporting the evidence that nTregs expressing the WT-FOXP3 allele have a selective advantage.…”
Section: Carriers Of Foxp3 Mutations Have Functionally Normal Ntregs mentioning
confidence: 65%
“…Overall, 100% donor T-cell chimerism was achieved in two out of five patients, and three have mixed donor chimerism. It has been reported that mixed chimerism, with only donor Treg population, is sufficient to suppress the autoimmune process and resolve enteropathy, 6,8 although it may take a long time because of previous severe gut damage. The patients' complex management was achieved by rigorous multi-disciplinary teamwork emphasizing the importance of managing this group of children in specialized centres.…”
mentioning
confidence: 99%
“…Therefore, while the functional impairment of FOXP3-mutated Treg cells is undisputed, the identification of circulating cells with figure. specific demethylation of the Treg-cell-Specific-Demethylated-Region (TSDR) (see below), demonstrated that wild type FOXP3 is dispensable for thymic development of Treg cell precursors in humans [44,55]. The lack of functional FOXP3 impairs Treg peripheral maintenance, as demonstrated by the observation that in healthy female carriers of FOXP3 mutations [102] and in transplanted IPEX patients with low peripheral donor chimerism [48] only Treg cells expressing a wild type FOXP3 are detectable in peripheral blood.…”
Section: Thymic Development Of Foxp3-mutated Ttreg Cellsmentioning
confidence: 99%
“…On the other hand, a non-myeloablative conditioning may increase the risk of a partial chimerism, although we now know that full donor engraftment is not necessary for complete recovery, but rather the engraftment of donor Treg cells is essential to cure the disease [48]. Based on the latter observation, cell/gene therapy approaches designed to selectively restore the Treg cell compartment are currently under investigation by the group of R. Bacchetta at the San Raffaele Scientific Institute of Milan, Italy, as an alternative therapeutic strategy when a suitable donor for HSCT is not available (Passerini et al, manuscript in preparation).…”
Section:  L Passerini Et Almentioning
confidence: 99%